NILAI EKONOMI EKOSISTEM LAMUN DI KOTA BONTANG - Nurul Ovia Oktawati; Erwan Sulistianto; Wahyu Fahrizal; Freddy Maryanto (EnviroScienteae, 2018)
Seagrass is one of the important ecosystems in shallow coastal and marine waters, because it has many roles, both ecologically and economically. Bontang City is one area that has a vast seagrass ecosystem. Management of seagrass ecosystems in Bontang City, of course, wants the existence of sustainable economic development, but on the other hand, sometimes increasing economic needs based on natural resources (resource base), often create a dilemma for the sustainability of natural resources. This happens because the consumption needs of the community are often not supported by good planning and management in utilizing natural resources so that the deterioration of environmental quality is often seen as a cost that must be paid in a process of economic development. The purposes of this study are 1). Identifying forms of utilization from seagrass ecosystems, 2) knowing the economic value of seagrass ecosystems. The sampling method used was purposive sampling. The results of the study revealed that fishing activities with splint catches and nets were a form of seagrass ecosystem utilization activities. Based on the results of data analysis, it is known that the total economic value of 4 (four) utilization of seagrass ecosystems in Bontang City is Rp. 7,081,050,816,042 per year. The utilization value with the largest proportion comes from the value of indirect benefits which is equal to 95.66%, and the lowest proportion is the option value.